PENGARUH METODE PEMBAYARAN PAY LATER DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN PRODUK (Studi Kasus Pada Mahasiswa S1 Akuntansi Angkatan 19 dan 20 UPN Veteran Jakarta): Studi Kasus Pada Mahasiswa S1 Akuntansi Angkatan 19 dan 20 UPN Veteran Jakarta - Nur Alfi Urfiah; Zulfa Kamila; Yasmin Aulia Syarifah (Politeknik Negeri Jakarta, 2023)
Seeing the rapid technological developments in the economic sector at this time, as well as the incessant Pay Later that is served by almost all E-commerce will have an impact on product purchasing decisions from consumers, especially from students who are tempted to use Pay Later because it can be a solution when income is low. stable but still have to meet the needs. However, with all the conveniences offered by Pay Later, students often get complacent and use Pay Later to buy consumables at high prices without paying attention to the added value of these items, that is, only to fulfill a high lifestyle. This study aims to determine the effect of using Pay Later and lifestyle on product purchasing decisions for S1 Accounting Students Batch 2019 and 2020 UPN Veteran Jakarta who are actively shopping online at E-commerce. After distributing the questionnaires, 83 respondents were obtained who participated and then became the sample in this study. The research method used is a quantitative method using a questionnaire method tested with a Likert scale. The results show that the Pay Later has an influence on product purchasing decisions, as well as the Lifestyle which also has an influence on purchasing decisions, which means that Pay Later and Lifestyle Accounting Students have a large influence on their purchasing decisions regardless of basic financial intelligence. acquired during the study period.